Implementation Of Extreme Programming Method In Financial Reporting Application With Laravel Framework - Akhmad Syukron; Andria Bas Nando; Sardiarinto; Eko Saputro (NUANSA INFORMATIKA, 2026)
The advancement of information technology compels companies to adopt more efficient, accurate, and integrated approaches to financial data management. CV Mawar Magenta, a service-oriented company, still relies on manual bookkeeping and separate Microsoft Excel files for financial reporting. This method leads to duplicate tasks, a high risk of data entry errors, and delays in generating financial reports. To address these issues, a web-based Financial Reporting Application was designed and developed using the Laravel Framework. The system development employed the Extreme Programming (XP) methodology and includes core features such as cash inflow and outflow records, general journal, ledger, profit and loss reports, and balance sheet. The system was tested using the black-box testing method to ensure all functionalities align with user requirements. The implementation results show that the application simplifies financial record-keeping by integrating previously separate processes into a single system. Additionally, it streamlines data retrieval and enables business owners to monitor financial conditions in real time, thereby supporting faster and more accurate decision-making.